Slope Stability Assessment along Qalachwalan-Suraqalat Main Road, Sulaimani, NE-Iraq - Ghafor A. Hamasur; Nzho M. Qadir (Tikrit Journal of Pure Science, 2020)
Rock failures are extremely frequent along the cut slopes of the road in the mountainous terrains of the Iraqi Kurdistan region. Qalachwalan – Suraqalat road which is to the north of Sulaimani city is one of the major transportation ways between Sulaimani city and many towns and villages of Sharbazher district. Sometimes, this road (especially in winter and spring seasons) shows many rock failures that causing hazards for locals and traffics. Therefore, the stability assessment of road-cut slopes along such road is very necessary.